2013
DOI: 10.1097/inf.0b013e31829ba34b
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability and Feasibility of Routine Pediatric HIV Testing in an Outpatient Clinic in Durban, South Africa

Abstract: Background Limited access to HIV testing of children impedes early diagnosis and access to antiretroviral therapy. Our objective was to evaluate the feasibility and acceptability of routine pediatric HIV testing in an urban, fee-for-service, outpatient clinic in Durban, South Africa. Methods We assessed the number of patients (0–15 years) who underwent HIV testing upon physician referral during a baseline period. We then established a routine, voluntary HIV testing study for pediatric patients, regardless of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
1
12
0
3
Order By: Relevance
“…Our study adds to existing literature showing a high prevalence of HIV amongst older children in sub-Saharan Africa, justifying the need for PITC in this population [40]. It highlights the missed opportunities for HIV testing of older children, and identifies opportunities to facilitate implementation of PITC for this age group (Box 1).…”
Section: Discussionmentioning
confidence: 57%
“…Our study adds to existing literature showing a high prevalence of HIV amongst older children in sub-Saharan Africa, justifying the need for PITC in this population [40]. It highlights the missed opportunities for HIV testing of older children, and identifies opportunities to facilitate implementation of PITC for this age group (Box 1).…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies among older children in Zimbabwe and South Africa found HIV prevalence ranging from 3% to 15% depending on the age group and study population [11],[12]. Most older children identified as infected have prior missed opportunities for earlier diagnosis, e.g., a known HIV-infected parent or sibling, previous tuberculosis treatment, hospital admission, or repeated presentation with minor infections [13][15].…”
mentioning
confidence: 99%
“…This finding is similar to provider-initiated counselling and testing (PITC) rates previously documented in other hospitals across sub-Saharan Africa. [27][28][29] Unfortunately, this is still a very low rate of PITC for an HIV endemic area, especially given the recommendations of many national and international guidelines, which advocate for increased PITC in HIV endemic areas in an effort to improve early recognition, optimise treatment and reduce new transmissions. 10 30 Moreover, we found that results were missing for more than one-quarter of children for whom a physician ordered HIV testing.…”
Section: Discussionmentioning
confidence: 99%